2004
DOI: 10.1111/j.1467-9507.2004.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relations among Observational, Physiological, and Self‐Report Measures of Children's Anger

Abstract: Our first goal was to examine the relations among observational, physiological, and self-report measures of children's anger. Our second goal was to investigate whether these relations varied by reactive or proactive aggression. Children (272 second-grade boys and girls) participated in a procedure in which they lost a game and prize to a confederate who cheated. Skin conductance reactivity, heart rate reactivity, selfreports of anger, angry facial expressions, and angry nonverbal behaviors were measured for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 73 publications
1
51
0
1
Order By: Relevance
“…Kochenderf-Ladd also found that young school-age victims were not angrier than non-victims but were more likely than non-victims to be motivated to seek revenge [20]. Among older children associations between subjective feelings and observable displays are weak to non-existent [21][22][23], although children with stronger motivation to maintain positive social interactions are less likely to display anger or aggression in response to provocation [24][25][26]. Taken together, the findings highlight the importance of examining motivation and feelings as indicators of subjective emotional experience and including a range of contexts in measures of emotion processes [27].…”
Section: Anger Managementmentioning
confidence: 89%
“…Kochenderf-Ladd also found that young school-age victims were not angrier than non-victims but were more likely than non-victims to be motivated to seek revenge [20]. Among older children associations between subjective feelings and observable displays are weak to non-existent [21][22][23], although children with stronger motivation to maintain positive social interactions are less likely to display anger or aggression in response to provocation [24][25][26]. Taken together, the findings highlight the importance of examining motivation and feelings as indicators of subjective emotional experience and including a range of contexts in measures of emotion processes [27].…”
Section: Anger Managementmentioning
confidence: 89%
“…In contrast, proactive aggression was not associated with anxiety and was unrelated to sleep problems once also considering the variance associated with reactive aggression. Proactive aggression is positively associated with callous-unemotional traits (i.e., a lack of guilt and remorse; Barry et al 2007;Fite et al 2009Fite et al , 2010 and unrelated to emotional arousal (Hubbard et al 2004(Hubbard et al , 2010. It appears that proactive aggression does not elicit the same negative emotions that produces anxiety (Fite et al 2010(Fite et al , 2012Raine et al 2006;Vitaro and Brendgen 2011) and ultimately results in sleep difficulties that reactive aggression elicits.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, proactive aggression has been linked to callous and unemotional traits (Barry et al 2007;Fite et al 2010;Fite et al 2009). Additionally, as stated above, only reactive aggression is positively linked to observable and physiological markers of emotional arousal (Hubbard et al 2004(Hubbard et al , 2010.…”
Section: Aggression and Sleep Problemsmentioning
confidence: 96%
See 1 more Smart Citation
“…In essence, higher levels of SCLR in the present study may be thought of as the body metabolically stepping up to the plate to deal with the demands of the present situation. It is possible, however, that higher or excessive SCLR elicited by a more threatening or anxiety-inducing stressor would be maladaptive, as excessive SCLR may reflect high levels of anxiety (Beauchaine 2001) or anger (Hubbard et al 2004). Therefore, it would be informative for future research to examine possible quadratic associations between SCLR responses and social competence using stressors that elicit higher levels of emotional arousal and larger physiological responses.…”
Section: Discussionmentioning
confidence: 96%